MEMAHAMI URGENSI PERADILAN MILITER DARI SUDUT KEPENTINGAN PERTAHANAN DAN KEAMANAN NEGARA - Supriyatna, S (Jurnal Yuridis, 2014)
This paper aims to understand the urgency of the military court of the interest of national defense and security. Political law in the reform era requires Army personnel (TNI) who commit criminal acts of the general public subject to the judicial authority. In peacetime, this understanding is acceptable, but when faced with a legal interest that reaches to the front (ius constituendum), which is in effect a state of danger, especially the state of war, it would be difficult to accept this understanding. In this context, the existence and role of Military Justice is very important in ensuring the interests of national defense and security. To give an idea of contextual understanding, this paper described it through discussion by a review of theoretical, philosophical, sociological, and juridical.